2016
DOI: 10.3346/jkms.2016.31.12.1863
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics and Risk Factors of Dengue Infection in Korean Travelers

Abstract: Dengue viral infection has rapidly spread around the world in recent decades. In Korea, autochthonous cases of dengue fever have not been confirmed yet. However, imported dengue cases have been increased since 2001. The risk of developing severe dengue in Korean has been increased by the accumulation of past-infected persons with residual antibodies to dengue virus and the remarkable growth of traveling to endemic countries in Southeast Asia. Notably, most of imported dengue cases were identified from July to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
2
11
1
1
Order By: Relevance
“…In our study, very few children aged 8 years or less were positive for dengue antibodies, whereas 63% of adults between 21 and 49 years old were positive for these antibodies. The same trend regarding age has been reported from both neighboring and non‐neighboring countries like India , Bangladesh mainland China , Timor‐Leste , Korea and Nepal .…”
Section: Prevalence Of Dengue By Age Group and Sex And Percentage Of supporting
confidence: 77%
“…In our study, very few children aged 8 years or less were positive for dengue antibodies, whereas 63% of adults between 21 and 49 years old were positive for these antibodies. The same trend regarding age has been reported from both neighboring and non‐neighboring countries like India , Bangladesh mainland China , Timor‐Leste , Korea and Nepal .…”
Section: Prevalence Of Dengue By Age Group and Sex And Percentage Of supporting
confidence: 77%
“…Previous studies have described differences in dengue presentation based on sex. 18,[20][21][22] Nearly 56% of the participants in our study were female and these patients had a significantly higher rate of DWWS compared to men (43.1% vs 31.3%; Table 3). Although univariate analysis showed that females had an increased risk of developing DWWS, this risk was no longer significant when adjusted for age and pre-existing immunity to DENV (Table 3).…”
Section: Clinical Manifestations By Sexmentioning
confidence: 76%
“…Previous studies have described differences in dengue presentation based on sex . Nearly 56% of the participants in our study were female and these patients had a significantly higher rate of DWWS compared to men (43.1% vs 31.3%; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pada infeksi primer, kemungkinan besar tidak terlaporkan karena adanya konsep sakit di masyarakat, di mana apabila masih bisa melaksanakan tugas atau bekerja mereka merasa tidak sakit, sehingga tidak periksa pada fasilitas kesehatan dan tidak terlaporkan. Adanya konsep tersebut, maka kemungkinan pada saat terjadi peningkatan kasus, disebabkan adanya infeksi dengue sekunder dengan derajat keparahan yang tinggi, dan pada saat tersebut banyak masyarakat yang periksa di fasilitas kesehatan sehingga kasus DBD terlaporkan (Je et al, 2016;Sarasati, 2016).…”
Section: Hasilunclassified